Enhanced expression of a 35 kDa fragment of inter-alpha-trypsin inhibitor H4 in sera of healthy pregnant women and patients with hydatidiform mole - Mohamed, Emida (BioMed Central, 2013)
BACKGROUND: Accumulated data from previous studies appear to suggest a link between the overexpression of a 35 kDa fragment of serum inter-alpha-trypsin inhibitor H4 (ITIH4) with cancers that are associated with up-regulated levels of oestrogens. The truncated fragment was postulated to be a product of oestrogen-induced action of kallikrein on native ITIH4. The present lectin-based proteomic analyses were performed to assess the specificity of the 35 kDa fragment of ITIH4 as a potential cancer biomarker and determine whether it was also overexpressed in the sera of cancer-negative pregnant women who are known to have high levels of plasma oestrogens. RESULTS: Our results demonstrated that the 35 kDa fragment of ITIH4 was overexpressed in healthy pregnant women and patients with hydatidiform mole, relative to the controls. The serum oestradiol levels of both groups of pregnant subjects were also confirmed to be higher than those of the control women who were not pregnant. CONCLUSIONS: Overexpression of the 35 kDa fragment of ITIH4 was not restrictive to patients with cancers but also occurred in women who were pregnant and those diagnosed with hydatidiform mole. Our data implicate the limitation of the 35 kDa ITIH4 fragment as a cancer biomarker and its correlation with serum oestrogen levels.